2003
DOI: 10.1099/vir.0.18957-0
|View full text |Cite
|
Sign up to set email alerts
|

The major envelope protein, GP5, of a European porcine reproductive and respiratory syndrome virus contains a neutralization epitope in its N-terminal ectodomain

Abstract: A set of neutralizing monoclonal antibodies (mAbs) directed against the GP 5 protein of European type porcine reproductive and respiratory syndrome virus (PRRSV) has been produced previously (Weiland et al., 1999). This set reacted with a plaque-purified virus (PPV) subpopulation of Dutch isolate Intervet-10 (I-10), but not with the European prototype PRRSV LV. In order to map the neutralization epitope in the GP 5 protein of the PPV strain, the ORF5 nucleotide sequence of PPV was determined. When the amino ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
67
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(68 citation statements)
references
References 43 publications
0
67
1
Order By: Relevance
“…virus (48,53,76), has been reported to be the most heterogeneous PRRSV structural protein, and is disulfide linked at an invariant cysteine (located at LV aa 50) to an invariant cysteine of the M protein (aa 8) (11,55). The hypervariable region observed among type 2 PRRSV field isolates includes the signal peptide sequence and the distal portion of the ectodomain, and the variation observed in this region tends to affect the number of potential N glycosylation sites (Fig.…”
Section: Amino Acid Alterations In Europrrsv Nsp1␤ and Nsp2mentioning
confidence: 99%
“…virus (48,53,76), has been reported to be the most heterogeneous PRRSV structural protein, and is disulfide linked at an invariant cysteine (located at LV aa 50) to an invariant cysteine of the M protein (aa 8) (11,55). The hypervariable region observed among type 2 PRRSV field isolates includes the signal peptide sequence and the distal portion of the ectodomain, and the variation observed in this region tends to affect the number of potential N glycosylation sites (Fig.…”
Section: Amino Acid Alterations In Europrrsv Nsp1␤ and Nsp2mentioning
confidence: 99%
“…Quality control for PRRSV cannot be performed using the same methods as for HIV and influenza, because of the limited knowledge of PRRSV neutralizing epitopes. There are some neutralizing epitopes known on GP5 and GP4 [39,48,66] and there are possibly also neutralizing epitopes on GP3 [5], but it is not known if other important epitopes exist and which neutralizing epitopes are most important. Previous results from our lab showed that PRRSV neutralizing antibodies block infection by preventing the interaction of PRRSV with the internalization receptor sialoadhesin (Sn) on the target cells, macrophages [15,16,60,61].…”
Section: Introductionmentioning
confidence: 99%
“…To generate the GP 2a glycosylation mutants, pABV437 (referred to below as wt-LV) was used as a template, whereas pABV911 (referred to below as wt-NS, neutralizationsensitive) was used as a template to introduce an additional mutation in the GP 5 glycosylation mutants. The wt-NS virus is identical to PRRSV LV except that it has a proline residue at position 24 of the GP 5 protein, which enables recognition of the mutant GP 5 proteins by neutralizing mAb P10/a46 (Wissink et al, 2003). Individual parts were amplified with the forward or the reverse primer containing the desired mutation (for a detailed description of the primers, see Table 1) and the two mutated PCR products were hybridized together and amplified with two primers outside the mutated region.…”
mentioning
confidence: 99%
“…Monoclonal antibody (mAb) P10/a46, directed against amino acids 29-35 of the GP 5 protein of the PPV strain (Wissink et al, 2003), was generously provided by Dr E. Weiland, Tübingen, Germany. mAb 122.17 is directed against the PRRSV N protein (van Nieuwstadt et al, 1996).…”
mentioning
confidence: 99%